Gaza Theory: Writing from Beneath the Rubble - Safaa Haqi (Hasanuddin University, 2026)
In a global context where suffering is often reduced to fleeting headlines and the voice of the oppressed is increasingly marginalized, Gaza Theory: Writing from Beneath the Rubble emerges as a contemporary literary and critical framework for reading texts produced under siege, occupation, and destruction. While rooted in the Palestinian experience, the theory transcends geography, proposing a universal lens through which literature written from within human catastrophe can be interpreted. Gaza, in this theory, is not merely a location—it is a symbolic and existential condition. The theory introduces key concepts such as